Evaluation of Co-promoted Ni/Al2O3 Catalyst for CO2 Reforming of Ethanol - Mahadi, Bahari; Ming, Fiona-Ling W.; Fayaz, Fahim; Nurul, Ainirazali; Phuc, Nguyen Huu Huy; Vo, Dai-Viet N. (Asian Research Publishing Network (ARPN), 2016)
The performance of Co-promoted Ni/Al2O3 catalyst prepared by co-impregnation method has been investigated for syngas generation through ethanol dry reforming in a tubular fixed-bed reactor at 973 K and various partial pressures of reactants. Both γ-Al2O3 support and 3%Co-10%Ni/Al2O3 catalyst exhibited high surface area of 174.13 and 89.15 m2 g-1, respectively. Temperature-programmed calcination and XRD measurements detected the formation of NiO, Co3O4, NiAl2O4 and CoAl2O4 phases on catalyst surface. In addition, the activation energy for the formation of these phases varied from 148.5 to 296.5 kJ mol-1. The conversion of both C2H5OH and CO2 was stable with time-on-stream at beyond 6 h. An increase in CO2 partial pressure enhanced the selectivity of H2 and CO but decreased CH4 selectivity due to the dry reforming reaction of CH4 intermediate product. The optimal C2H5OH partial pressure was obtained at 30 kPa in terms of H2 and CO yield.